Teaching simple present tense trough games - Vinansaca Trelles, Ruth; Yanzaguano, Sandra
TEACHING SIMPLE PRESENT TENSE TROUGH GAMES Nowadays, games are designed to teach people about a certain subject, expand concepts, reinforce development, understand an historical event or culture, or assist them in learning a skill as they play. Games are not activities mainly aimed to break the ice between students or to kill time. They should be enjoyed and fun. They are not just a diversion, a break from routine activities, but a way of getting the learner to use the language in the course of the game.? Byrne (1995)? When using games in the classroom, it is beneficial for teachers to have a complete understanding of the definitions of games, which usually are defined as a form of play concerning rules, competition, and an element of fun. Teachers should also consider the advantages of games: the ability to capture students